2019
DOI: 10.1038/s41598-019-48276-0
|View full text |Cite
|
Sign up to set email alerts
|

Sinus node-like pacemaker mechanisms regulate ectopic pacemaker activity in the adult rat atrioventricular ring

Abstract: In adult mammalian hearts, atrioventricular rings (AVRs) surround the atrial orifices of atrioventricular valves and are hotbed of ectopic activity in patients with focal atrial tachycardia. Experimental data offering mechanistic insights into initiation and maintenance of ectopic foci is lacking. We aimed to characterise AVRs in structurally normal rat hearts, identify arrhythmia predisposition and investigate mechanisms underlying arrhythmogenicity. Extracellular potential mapping and intracellular action po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Here, we show that the healthy, denervated ex vivo isolated rat and human RA both exhibit 2 distinct clusters of functional pacemaking activity specifically located near the SVC and IVC—denoted here as the sSAN and iSAN—which preferentially control high and low HRs, respectively ( Central Illustration ). Previous reports from various species ( 3 , 12 , 29 33 ) have also demonstrated that leading pacemaker sites can and generally do move toward an inferior location within the SAN with high vagal tone (in addition to activity from the atrioventricular node or atrioventricular ring) ( 34 ), but this inferior, or “backup,” pacemaker located near the IVC has not yet been fully characterized. With the application of state-of-the-art optical mapping and novel signal processing techniques on a beat-to-beat basis, we observed a clear phenomenon of 2 distinct RA pacemaking regions over the entire range of SAN-initiated physiological HRs in the healthy rat heart and over a normal range of physiological HRs in the healthy human heart.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show that the healthy, denervated ex vivo isolated rat and human RA both exhibit 2 distinct clusters of functional pacemaking activity specifically located near the SVC and IVC—denoted here as the sSAN and iSAN—which preferentially control high and low HRs, respectively ( Central Illustration ). Previous reports from various species ( 3 , 12 , 29 33 ) have also demonstrated that leading pacemaker sites can and generally do move toward an inferior location within the SAN with high vagal tone (in addition to activity from the atrioventricular node or atrioventricular ring) ( 34 ), but this inferior, or “backup,” pacemaker located near the IVC has not yet been fully characterized. With the application of state-of-the-art optical mapping and novel signal processing techniques on a beat-to-beat basis, we observed a clear phenomenon of 2 distinct RA pacemaking regions over the entire range of SAN-initiated physiological HRs in the healthy rat heart and over a normal range of physiological HRs in the healthy human heart.…”
Section: Discussionmentioning
confidence: 99%
“…V m was recorded at 10 kHz with the PowerLab data acquisition device controlled by LabChart (ADInstruments, Colorado Springs, CO, United States). From the V m recordings, characteristics of the SAN, atrial, and ventricular cell AP were calculated, using custom routines in Matlab following previously described algorithms ( Bucchi et al, 2007 ; Logantha et al, 2019 ). For the SAN, these included: (i) maximum diastolic potential (MDP), defined as the most negative V m reached during AP repolarisation; (ii) slope of DD, defined as the change in V m over the time between the point of MDP and the initiation of the AP, which was determined as the point at which the rate of change of V m was greater than 500 mV/s; (iii) maximum rate of change of V m during the upstroke (dV/dt max ); (iv) maximum V m during the AP; (v) AP amplitude, defined as the change in V m between the initiation and peak of the AP; and (vi) AP duration at 50% (APD 50 ) and 80% (APD 80 ) repolarisation, defined as the time between the initiation of the AP and the restoration of V m from peak to 50% or 80% of MDP.…”
Section: Methodsmentioning
confidence: 99%
“…The decreased amplitude and increased PRi is consistent with the slowing of atrial conduction, likely due to the actions of acetylcholine on atrial M2 muscarinic receptors following increases in reflex parasympathetic activity (Hooper et al, 2019). Notched or negative P waves are likely ectopic atrial beats (Waldo et al, 1975), and this is consistent with heterogeneity of conduction throughout the rat atria and pacemaker activity near the rat pulmonary vein (Masani, 1986;Maupoil et al, 2007;Fan et al, 2019;Logantha et al, 2019). AITC inhalation caused an increase in negative P waves in SH rats but not WKY rats, despite the observation that AITC-evoked increases in PRi were similar between the strains and AITC-evoked increases in RRi and Pwidth were greater in the WKY rat (Figures 3, 4).…”
Section: Discussionmentioning
confidence: 58%